The Role of Transformational Leadership in Enhancing Organizational Success: An Analytical Study of the Opinions of a Sample of Individuals Working in a Number of Food Factories in the City of Erbil. - معروف جميل, بريشان; محمود عبدالله, شفان (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The general framework: The study used, through its general framework, to define the research problem, several questions related to the nature of the relationship and the influence between the independent variable represented by transformational leadership and the dependent variable represented by organizational success, where the hypothetical scheme of the study was developed, which consisted of four main hypotheses, and for the purpose of verifying the validity of the hypotheses, all of them were subject to analyses. Statistics and many tests using the statistical analysis program (SPSS V.26). The arbitrators and statistical methods were used for the purpose of verifying the validity and stability of the questionnaire, the simple and multiple linear regression, as well as the correlation. Objective: The current research aims to know the role of transformational leadership in promoting organizational success. Where the dimensions of the independent variable included transformational leadership (ideal influence (charisma), motivation, intellectual stimulation, and individual considerations), while the dimensions of organizational success were (efficiency, effectiveness). Research methodology: The research used the descriptive approach for the purpose of describing the main variables, and using the analytical approach to analyze the relationships and correlation between the variables of the study and its dimensions used in the research. (168) individuals, and the number of questionnaires valid for statistical analysis was (142) individuals. Conclusions and Suggestions: The study reached a number of conclusions, most notably the existence of a significant and direct correlation with high levels between transformational leadership and organizational success according to the macro and partial levels, which indicates that the more the studied food factories use transformational leadership, the more this leads to strengthening its method in promoting organizational success. With a significant impact relationship of the transformational leadership variable on the organizational success variable, which indicates that the dependence of the researched food factories on transformational leadership affects the promotion of a high level of organizational success for them. One of the most important proposals that he reached is the need to strengthen the weak relationship, and in particular the impact of intellectual stimulation on organizational success through the researched food factories stimulating the efforts of workers and benefiting from their potential and knowing the extent of their awareness in problem-solving and creativity at work.